Dermoscopic Discoveries in Psoriasis and Seborrheic dermatitis on the scalp and Relationship with Malady Seriousness: The systematic Review and Meta-analysis - Dabukke, Yeyen Jani Sari (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Dermoscopy has regularly been utilized for hair and scalp clutters. Dermoscopic examinations of psoriasis and seborrheic dermatitis injuries yielded diverse morphologies. This ponder pointed to examine the value of dermoscopy within the clinical separation of psoriasis and seborrheic dermatitis on the scalp and furthermore to assess its capacity in deciding illness seriousness. Method: This study using systematic review that search using keyword Psoriasis, Seborrheic Dermatitis and Dermoscopic Findings. Result: After final screening the author analysize 5 articles. As in methods, the author summarize 2 articles. Conclussion: dermoscopy could be a important and easy-to-use device for separating psoriasis and seborrheic dermatitis on the scalp indeed on the off chance that it doesn’t have sufficient strength to determine malady seriousness. In expansion, there's a few differences and uncertainty concerning phrasing, which can be settled with future thinks about and the foundation of conventional terms.